Powdery Mildew Resistance Genes in European Barley Cultivars Registered in the Czech Republic from 2016 to 2020 - Dreiseitl, Antonín (Genes, 2022)
Barley is an important crop grown annually on about 55 Mha and intensively cultivated in Europe. In central and north-western Europe, spring and winter barley can be grown in similar environments which creates suitable conditions for the development of barley pathogens, including Blumeria graminis f. sp. hordei, the causal agent of powdery mildew. Apart from pesticide application, it can be controlled by inexpensive and environmentally-friendly genetic resistance. In this contribution, results of the resistance gene identification in 58 barley cultivars to powdery mildew are presented. In 56 of them their resistances were postulated and in two hybrid cultivars a recently developed method of gene identification was used. In total, 18 known resistance genes were found and several unknown genes were detected. In spring barley, a gene of durable resistance mlo is still predominant. MlVe found in winter SU Celly was the only new resistance gene recorded in barley cultivars registered in the Czech Republic in this time span. Since 2001 eight new genes of specific resistance have been identified in cultivars registered in the country and their response under field conditions is discussed, including the corresponding responses of the pathogen population due to directional selection. Different strategies for breeding spring and winter barley are recommended.
Keywords: Hordeum; Česká republika; nemoci rostlin; resistance gene postulation; Czech Republic; Evropa; Europe; šlechtění rostlin; Plant Breeding; Plant Diseases; infection response arrays; Blumeria graminis f. sp. hordei; pathogen isolates; Hordeum vulgare; ječmen (rod)